A Novel HLA–DRB1*10:01–Restricted T Cell Epitope From Citrullinated Type II Collagen Relevant to Rheumatoid Arthritis. Issue 5 (27th April 2016) - Chemin, Karine; Pollastro, Sabrina; James, Eddie; Ge, Changrong; Albrecht, Inka; Herrath, Jessica; Gerstner, Christina; Tandre, Karolina; Sampaio Rizzi, Thais; Rönnblom, Lars; Catrina, Anca; Holmdahl, Rikard; et al.
Abstract : Objective: Antibodies against citrullinated type II collagen (Cit‐CII) are common in the sera and synovial fluid of patients with rheumatoid arthritis (RA); however, the known T cell epitope of CII is not dependent on citrullination. The aim of this study was to identify and functionally characterize the Cit‐CII–restricted T cell epitopes that are relevant to RA. Methods: Peripheral blood mononuclear cells (PBMCs) from HLA–DRB1*10:01–positive patients with RA and healthy donors were stimulated in vitro with candidate CII peptides. CD154 up‐regulation was measured as a marker of antigen‐specific activation, and anti–HLA–DR–blocking experiments confirmed HLA restriction. Cytokine production was measured using a Luminex technique. Direct peptide‐binding assays using HLA–DRB1*10:01 and HLA–DRB1*04:01 monomeric proteins were performed. The T cell receptor (TCR) β‐chain of CD154‐enriched antigen‐specific T cells was analyzed using high‐throughput sequencing. Results: A novel Cit‐CII peptide was identified based on its ability to activate CD4+ T cells from HLA–DRB1*10:01–positive individuals. When stimulated in vitro, Cit‐CII autoreactive T cells produced proinflammatory cytokines. Cit‐CII 311–325 bound (with low affinity) to HLA–DRB1*10:01 but not to HLA–DRB1*04:01, while the native form was unable to bind either protein. In addition, highly expanded clones were identified in the TCRβ repertoire of Cit‐CII 311–325 –stimulated PBMCs. Conclusion: These results illustrate the ability of the citrullination process to create T cell epitopes from CII, a cartilage‐restricted protein that is relevant to RA pathogenesis. The exclusive binding of Cit‐CII 311–325 to HLA–DRB1*10:01 suggests that recognition of citrullinated epitopes might vary between individuals carrying different RA‐associated HLA–DR molecules.